Investment decision analysis of heavy equipment at PT Mandrosa Sukses - Haris Santoso; Sylviana Maya Damayanti (Institute of Computer Science (IOCS), 2024)
Excavators are one type of heavy equipment that enables a variety of tasks such as digging, trenching, excavating, and loading trucks. It also helps move, lift, and place materials, such as stone and drainage products. Therefore, excavators are considered the most important heavy equipment in road construction projects. This research analyzed the feasibility of investment by calculating financial indicators in PT Mandrosa Sukses. This research aimed to determine and assess the feasibility of the excavator investment quantitatively from the financial aspect. This research used the quantitative approach to fulfill the research objectives. The parameters used to review these investments are the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Benefit Cost Ratio (BCR) methods. The analysis generates an NPV of IDR 597,874,848, an IRR of 26.23%, and a Payback Period of 4.08 years. Based on the cost benefit analysis, the purchasing option results in a BCR of 1.08 and the renting option results in a BCR of 1.02. it can be concluded that purchasing an excavator is a better option than renting an excavator